RETRACTED: Study of the penetrating ability of 5% glucose solution into insulin–dependent cells of mouse organs, under the influence of ionising radiation - Mirsaeva F.Z.; Garaishin R.M.; Kzyrgalin S.R.; Kitapova R.R.; Kostromina D.A.; Garaishina D.R.; Zaleev T.R. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001